Implementasi Konseling REBT dalam Rangka Mengarahkan Meaning Of Life Remaja - Aiwani, Aisyiah; Nate, Mahara Pinte; Hasanah, Binti Uswatun; Munir, Ah. Fahri; Fahira, Ihza Chaidaratul; Kaesti, Mutiarani R. D. E (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2023)
Highlighting the mechanism in the meaning of life of adolescents, it was found that they had not yet mastered matters related to directing a view of life so that things were needed that could be used as reinforcement so that adolescents did not misinterpret things shown by people in their environment. In response to this, the researcher aims to conduct research with a library research design related to the Implementation of REBT Counseling in directing the meaning of life of adolescents. The results obtained from the search by researchers are to direct adolescents who are at an unstable age, assistance is needed for the adolescents themselves. Assistance can be done by adults such as parents, teachers and counselors. Basically, the classification of rational and irrational thoughts is done so that the counselee is able to understand in advance which path is good to take as a guide to the meaning of life. In addition, the counselor also needs to challenge the counselee to test his thoughts. If indeed there are some rational thoughts that are chosen as a path by the counselee, the counselor does not immediately say yes, but the counselor also needs to play a role in opposing what the counselee conveys to measure his understanding of the meaning of life he chooses.